Hubungan antara pengetahuan gizi, aktivitas fisik, dan intensitas olahraga dengan status gizi - Roring, Natalia Megawati; Posangi, Jimmy; Manampiring, Aaltje Ellen (UNIVERSITAS SAM RATULANGI, 2020)
Abstract: The purpose of this research to determine the relationship between nutritional knowledge, physical activity with exercise intensity and nutritional status. The method used is quantitative research with the approach cross sectional study. Determination of sample was done by total sampling totaled 118 Church youth GMIM Kanaan Pinabetengan. Analysis of test data using spearman correlation coefficient. The results showed the nutritional status of the most many categories of normal 43.3%, fat 29.9%, skinny 26.9%. Knowledge of nutrition both categories 56.7%, less good 43.3%. Physical activity in the category of pretty 53.7%, less 46.3%. The intensity of the sport category better 55.2%, less good 44.8%. Spearman test between nutritional knowledge and nutritional status are known to have a relationship, be aware the value of significant (2tailed), namely 0.003. The strength of the relationship moderates the positive direction. Spearman test between physical activity and nutritional status are known to have a relationship, be aware the value of significant (2tailed), namely 0.003. The strength of the relationship moderates the positive direction. Spearman test between intensity of exercise and nutritional status are known to not have a relationship. The conclusion there is a relationship between knowledge of nutrition, physical activity and nutritional status. There is no relationship between exercise intensity and nutritional status on the youth of the Church GMIM Kanaan Pinabetengan.Keywords: knowledge, physical activity, exercise intensity, nutritional statusÂ Â Abstrak: Penelitian ini bertujuan mengetahui hubungan antara pengetahuan gizi, aktivitas fisik dengan intensitas olahraga dan status gizi. Metode yang digunakan yaitu penelitian kuantitatif dengan pendekatan cross sectional study. Penentuan sampel dilakukan secara total sampling berjumlah 118 pemuda Jemaat GMIM Kanaan Pinabetengan. Analisis data menggunakan uji koefisien korelasi spearman. Hasil penelitian menunjukkan status gizi paling banyak kategori normal 43.3%, gemuk 29.9%, kurus 26.9%. Pengetahuan gizi kategori baik 56.7%, kurang baik 43.3%. Aktivitas fisik pada kategori cukup 53.7%, kurang 46.3%. Intensitas olahraga kategori baik 55.2%, kurang baik 44.8%. Uji spearman antara pengetahuan gizi dengan status gizi diketahui memiliki hubungan, diketahui nilai signifikan (2tailed) yaitu 0.003. Kekuatan hubungan moderat arah positif. Uji spearman antara aktivitas fisik dengan status gizi diketahui memiliki hubungan, diketahui nilai signifikan (2tailed) yaitu 0.003. Kekuatan hubungan moderat arah positif. Uji spearman antara intensitas olahraga dengan status gizi diketahui tidak memiliki hubungan. Simpulan ada hubungan antara pengetahuan gizi, aktivitas fisik dengan status gizi. Tidak ada hubungan antara intensitas olahraga dengan status gizi pada pemuda Jemaat GMIM Kanaan Pinabetengan.Kata kunci: pengetahuan, aktivitas fisik, intensitas olahraga, status gizi